(untitled) (Global Journal of Medical Research, 2023)
Background Operations of total hip and knee arthroplasty are currently one of the most frequent surgical interventions performed for the purpose of functional rehabilitation of patients with osteoarthritis or patients who have received a fracture of the femoral neck The best method for providing anesthesia and pain relief for total joint replacement has not been determined Until now a unified point of view on the choice of the optimal method of anesthesia and analgesia in surgical interventions for arthroplasty has not been formed Purpose of the study To study the effectiveness of caudal anesthesia in hip and knee arthroplasty Material and research methods The study was conducted in the surgical clinic of the AMU in 56 patients who underwent surgery for hip and knee arthroplasty The age of the patients varied from 57 to 99 years